2020
DOI: 10.3390/v12070772
|View full text |Cite
|
Sign up to set email alerts
|

Brothers in Arms: Structure, Assembly and Function of Arenaviridae Nucleoprotein

Abstract: Arenaviridae is a family of viruses harbouring important emerging pathogens belonging to the Bunyavirales order. Like in other segmented negative strand RNA viruses, the nucleoprotein (NP) is a major actor of the viral life cycle being both (i) the necessary co-factor of the polymerase present in the L protein, and (ii) the last line of defence of the viral genome (vRNA) by physically hiding its presence in the cytoplasm. The NP is also one of the major players interfering with the immune system. Several struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 124 publications
(178 reference statements)
0
19
0
Order By: Relevance
“…NPs potentially can assemble around random RNA or ssDNA to form nucleoprotein particles 21 similar to the native conformation in virus. Howerer, recent studies demonstrate that significant conformational changes are nessesary for RNA encapsidation 22 , 23 . The role of NP in lifecyle of virus including replication, transcription and assembly are important but little data is available regarding the precise mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…NPs potentially can assemble around random RNA or ssDNA to form nucleoprotein particles 21 similar to the native conformation in virus. Howerer, recent studies demonstrate that significant conformational changes are nessesary for RNA encapsidation 22 , 23 . The role of NP in lifecyle of virus including replication, transcription and assembly are important but little data is available regarding the precise mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It was puzzling though, because a NTP was captured in the RNA binding domain in a closed conformation. Further studies have observed that significant conformational changes are necessary to encapsidate the genomic RNA [6], and as part of the Bunyavirales and structural similarities with Nairovirus , arenaviruses NP should follow one of the four mechanism of multimerization [4]. Shortly, all Bunyavirales NP structures described until now, present a globular core domain, which, harbors the RNA binding cleft.…”
Section: Figmentioning
confidence: 99%
“…The arenaviruses NP is the mandatory cofactor of the L protein for both transcription/replication processes, it protects passively and actively the genome/antigenome from cellular host defense enzymes, and finally, it packages the genome. These functions are reflected in the structural architecture of NP as a two domain protein surrounded by two flexible linkers : In amino terminal, the NP core domain (NP‐core) involved in polymerization and vRNA protection; in carboxy terminal, the exonuclease domain (ExoN) involved in degrading dsRNA, a marker of viral infection [4]. The sequence of NP is well conserved among arenaviruses (21% identity and ~ 80% similarity) and thoroughly along the NP structure (Fig.…”
Section: Figmentioning
confidence: 99%
“…Because of its biological significance to the viral life cycle and role in infectious processes, arenavirus and coronavirus ExoN is an attractive target for drug development (Papageorgiou et al, 2020; Subissi et al, 2014). Currently, there are almost no FDA-approved antivirals against these viruses, despite the loss of human lives during the short-lived SARS-CoV outbreak in 2002 and the continuing MERS epidemic or regular outbreaks of LASSA virus in West Africa causing several thousand case fatalities.…”
Section: Introductionmentioning
confidence: 99%